Conceptualization of Karstic Aquifer with Multiple Outlets Using a Dual Porosity Model. Issue 4 (16th February 2017) - Hosseini, Seiyed Mossa; Ataie‐Ashtiani, Behzad
Abstract: In this study, two conceptual models, the classic reservoir (CR) model and exchange reservoirs model embedded by dual porosity approach (DPR) are developed for simulation of karst aquifer functioning drained by multiple outlets. The performances of two developed models are demonstrated at a less developed karstic aquifer with three spring outlets located in Zagros Mountain in the south‐west of Iran using 22‐years of daily data. During the surface recharge, a production function based on water mass balance is implemented for computing the time series of surface recharge to the karst formations. The efficiency of both models has been assessed for simulation of daily spring discharge during the recession and also surface recharge periods. Results indicate that both CR and DPR models are capable of simulating the ordinates of spring hydrographs which drainage less developed karstic aquifer. However, the goodness of fit criteria indicates outperformance of DPR model for simulation of total hydrograph ordinates. In addition, the DPR model is capable of quantifying hydraulic properties of two hydrologically connected overlapping continua conduits network and fissure matrix which lays important foundations for the mining operation and water resource management whereas homogeneous model representations of the karstic subsurface (e.g., the CR) do not work accurately in the karstic environment. Abstract : Article impact statement : Dual porosity reservoir model explains better representation of dynamic behavior and hydraulic properties of karst aquifers with multiple outlets than classic linear reservoir model.